Complications, caused by application of the net implants in the hiatal hernias plasty - V. V. Grubnik; Ya. S. Bereznytskyi; V. V. Ilyashenko; V. V. Grubnyk; D. V. Korchovyi; O. M. Kiosov (Клінічна хірургія)
Objective. Studying of complications, connected with application of the net implants in patients with large hiatal hernias.